Immunology. - Kuby, James, ....- (New York : Freeman, 1998)
Contents: --------- 1. Overview of the immune system 2. Experimental systems 3. Cells and organs of the immune system 4. Antigens 5. Immunoglobulins: structure and function 6. Antigen-antibody interactions 7. Organization and expression of immunoglobulin genes 8. B-cell maturation, activation and differentiation 9. Antigen processing and presentation 11. T-cell receptor 12. T-cell maturation, activation and differentiation 13. Cytokines 14. The complement system 15. Leukocyte migration and iinflammation 16. Xell-mediated and humoral effector responses 17. Hypersensitive reactions 18. Vaccines 19. Immune response to infectious diseases 20. Autoimmunity 21. Immunodeficiency diseases 22. The immune system in AIDS 23. Transplantation immunology 24. Cancer and the immune system
Keywords: Immunologie